Management of Axillary Web Syndrome after Breast Cancer: Evidence-Based Practice - Luz, Clarissa Medeiros da; Deitos, Julia; Siqueira, Thais Cristina; Palú, Marina; Heck, Ailime Perito Feiber (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Axillary web syndrome is characterized as a physical-functional complication that impacts the quality of life of women who have undergone treatment for breast cancer. The present study aims to verify the physiotherapy treatment available for axillary web syndrome after surgery for breast cancer in the context of evidence-based practice. The selection criteria included papers discussing treatment protocols used for axillary web syndrome after treatment for breast cancer. The search was performed in the MEDLINE, Scopus, PEDro and LILACS databases using the terms axillary web syndrome, lymphadenectomy and breast cancer, focusing on women with a previous diagnosis of breast cancer who underwent surgery with lymphadenectomy as part of their treatment. From the 262 studies found, 4 articles that used physiotherapy treatment were selected. The physiotherapy treatment was based on lymphatic drainage, tissue mobilization, stretching and strengthening. The four selected articles had the same outcome: improvement in arm pain and shoulder function and/or dissipation of the axillary cord. Although axillary web syndrome seems to be as frequent and detrimental as other morbidities after cancer treatment, there are few studies on this subject. The publications are even scarcer when considering studies with an interventional approach. Randomized controlled trials are necessary to support the rehabilitation resources for axillary web syndrome.
Keywords: physiotherapy; axillary web syndrome; conservative treatment; rehabilitation; cording; lymphadenectomy